Anatomía de la madera de doce especies del bosque mesófilo de montaña del Estado de México - Aguilar-Rodríguez, Silvia; Castro-Plata, Beatriz Jimena (Instituto de Ecología, A.C., 2016)
In this study the wood anatomical description of 12 species characteristics from cloud forest in the State of México was carried out. For each species the qualitative and quantitative microscopic characters of wood are described. On the basis of the Runkel relationship, the quality of their fibers is classified to obtain pulp for paper. The morphological characteristics of each species are given, as well as their common names and national distribution. Eight species have growth rings formed by bands of fibers with lumens reduced and thick walls, or compressed radially, in the late wood. The porosity is diffuse; the vessels are small, with less than 100 μm diameter, and numerous. Several species presented vessel elements with scalariform perforation plates. Vessel elements and fibers were medium and long. In general the axial parenchyma is scarce and in seven species the rays are heterogeneous type I. These results are similar to those obtained in other regions. According to the relationship of Runkel it was found out that the fibers are of medium to good quality for paper.